Genetic inhibition of solute-linked carrier 39 family transporter 1 ameliorates Aβ pathology in a Drosophila model of Alzheimer’s disease - Lang, Minglin; Wang, Lei; Fan, Qiangwang; Xiao, Guiran; Wang, Xiaoxi; Zhong, Yi; Zhou, Bing (My University, 2012)
The aggregation or oligomerization of amyloid-β (Aβ) peptide is thought to be the primary causative event in the pathogenesis of Alzheimer's disease (AD). Considerable in vitro evidence indicates that the aggregation/oligomerization of Aβ is promoted in the presence of Zn; however, the functional role of Zn in AD pathogenesis is still not well clarified in vivo. Zn is imported into the brain mainly through the solute-linked carrier (Slc) 39 family transporters. Using a genetically tractable Drosophila model, we found that the expression of dZip1, the orthologue of human Slc39 family transporter hZip1 in Drosophila, was altered in the brains of Aβ42-expressing flies, and Zn homeostasis could be modulated by forcible dZip1 expression changes. An array of phenotypes associated with Aβ expression could be modified by altering dZip1 expression. Importantly, Aβ42 fibril deposits as well as its SDS-soluble form were dramatically reduced upon dZip1 inhibition, resulting in less neurodegeneration, significantly improved cognitive performance, and prolonged lifespan of the Aβ42-transgenic flies. These findings suggest that zinc contributes significantly to the Aβ pathology, and manipulation of zinc transporters in AD brains may provide a novel therapeutic strategy.
Keywords: Amyloid-β; Alzheimer's disease; Solute-linked carrier 39 family transporters; Zinc transporters; Drosophila model